LEPTOSPIROSIS DENGAN GANGGUANG GINJAL : LAPORAN KASUS - Mujahidah; Subakir; Desvita Sari; Maria Estela Carolina (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2023)
Background: Leptospirosis is a public health problem throughout the world, especially in countries with tropical and subtropical climates and with high rainfall, such as Indonesia. Leptospirosis is a rat-originated disease that is classified as an emerging disease, caused by the Leptospira interrogans bacteria that are pathogenic to humans and animals. Leptospirosis can cause kidney problems due to toxins that can affect the immune system. Case report: A 56 year old woman with loss of consciousness, convulsions and fever. A positive Lateral flow examination and Microscopic Agglutination test (MAT) were carried out with the results showing Pomona serogroup, Pomona serovar, Pomona strain with a titer of 1:320 showing positive results. The results of examination of urea creatinine (6.5 mg/dl) and urea (234 mg/dl) showed a disturbance in the kidneys. Conclusion: Laboratory examinations in the form of Lateral flow and MAT showed Leptospira infection with renal impairment. Keywords: Leptospirosis, kidney disorders, Lateral flow, MAT